The THE RELATIONSHIP BEETWEN BURNOUT AND CARING BEHAVIOR AMONG ANESTHESIOLOGY NURSING STUDENTS IN PROVIDING PERIOPERATIVE ANESTHESIOLOGY NURSING CARE - Widyasti Thaib; Heri Puspito; Gatot Suparmanto (Keperawatan Anestesiologi Program Sarjana Terapan, 2026)
Background: Burnout is a psychological syndrome characterized by emotional exhaustion, cynicism, and a reduced sense of professional efficacy. Anesthesiology nursing students face substantial academic and clinical practice demands, placing them at risk of experiencing burnout. This condition may negatively affect their caring behavior when providing perioperative anesthesiology nursing care. Methods: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 61 eighth-semester students from the Nurse Anesthesiology Program at Universitas ‘Aisyiyah Yogyakarta, selected using a simple random sampling technique. Data were collected using the Maslach Burnout Inventory (MBI) and the Caring Behavior Inventory (CBI-24). Data analysis was conducted using the Spearman Rank correlation test. Results: The Spearman Rank test showed a correlation coefficient of -0.458 with a p-value of 0.000 (p < 0.05), indicating a significant negative relationship between burnout and caring behavior among anesthesiology nursing students. Higher levels of burnout were associated with lower levels of caring behavior in perioperative clinical practice. Most respondents experienced a moderate level of burnout (55.7%) and demonstrated a moderate level of caring behavior (60.7%). Conclusion: There is a significant correlation between burnout and caring behavior among anesthesiology nursing students in the provision of perioperative anesthesiology nursing care. Keywords: Burnout, Anesthesiology Nursing Students, Caring Behavior, Anesthesiology Nursing